L'étranger intime : Les traductions françaises de l'œuvre de Paul Celan (1971-2010). - Dueck, Evelyn (Communicatio., 2014)
For the first time, this study offers a detailed analysis of the translations of Paul Celan's poetry published in French from 1971 to 2010. In addition, the author proposes a new model for translating poetry and analyzing poetic translation that extends beyond the work of Celan and engages critically with existing methods. As a result, it becomes possible to read Paul Celan's poetry from an entirely new, foreign, and yet familiar perspective.